ON SOME ISSUES OF AVOIDANCE OF DOUBLE TAXATION - Dauren Hamitovich, Пернеев (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The author, considering the cases of double taxation, making a comparative analysis of some of its methods of removal, expresses the idea of the necessity of States concluding agreements on avoidance of double taxation, which will promote the development of international trade relations.